Notes of a Plenipotentiary : Russian Diplomacy and War in the Balkans, 1914-1917 - Trubet︠s︡koĭ, Grigoriĭ N. (Grigoriĭ Nikolaevich), kni︠a︡zʹ, 1873-1930 (Book collections on Project MUSE., 2016)
"A prince in one of Russia's most exalted noble families, Grigorii N. Trubetskoi was a unique and contradictory figure during World War I.A lifelong civil servant and publicist, he began his diplomatic career in Constantinople, where he served as first secretary of the embassy there for several years. He became one of the leaders of an important political orientation among the liberals that began to express opposition to the tsar, not only on questions of political freedom and domestic political reform, but also by criticizing the tsar's foreign policy on nationalistic grounds. Trubetskoi possessed significant influence over Russian foreign policy and was instrumental in pushing the regime toward an aggressive annexationist stand in the Balkans. When the Russian ambassador to Serbia died suddenly in June of 1914, Trubetskoi was appointed as his replacement--situating him at the center of Russian diplomacy during the decisive period of Russia's entry into the war. His account of this period serves as an important reference for the study of the war's outbreak. Trubetskoi also discusses how he drafted the proclamation on Poland and gives a revealing account of its origins. A valuable source on the major historical problem of the entry of Turkey into the war, the narrative provides interesting details about agreements with Britain and France. Translated by Trubetskoi's granddaughter, Elizabeth Saika-Voivod, and featuring Trubetskoi's original photographs, this fascinating memoir provides an inside look at Russian foreign policies during crucial points of the war. It will appeal to scholars, students, and general readers interested in World War I and Russian history"--